Loss-of-function mutations in the filaggrin gene: no contribution to disease susceptibility, but to autoantibody formation against citrullinated peptides in early rheumatoid arthritis. Issue 1 (17th August 2007) - Hüffmeier, U; Böiers, U; Lascorz, J; Reis, A; Burkhardt, H
Abstract : Objectives: Autoantibody formation to citrullinated (pro)filaggrin has proven to be a highly specific serological marker for rheumatoid arthritis (RA). To test the potential relevance of mutations of the filaggrin ( FLG ) gene for disease susceptibility and elicitation of humoural autoimmunity in RA, a case–control association study of three loss-of-function FLG variants was performed. Methods: DNA was obtained from 282 patients with early RA (mean disease duration: 6.5 months) and from 376 control individuals. Three loss-of-function variants of the FLG gene (*R501X, *2282del4 and *3702del1) were genotyped. Results: No significant differences in genotype frequencies were observed between control probands and the population of RA patients. The FLG *3702del1 allele was not identified in any of the patients nor controls, and none of the probands was homozygous or compound heterozygous. In the RA cohort, heterozygous carriers of either of the FLG variants exhibited a significantly elevated prevalence of autoantibodies to citrullinated peptides (CCP-2) (80%) compared to non-carriers (51.9%) (p = 0.018, odds ratio: 3.71 (1.20–11.46)). Conclusions: The investigated FLG variants do not confer an overall risk for the development of RA. However, loss-of-function mutations in the FLG gene may contribute to the development of humoural autoimmunity, targeting citrullinated determinants in early RA.